(untitled) (Bangladesh Journal of Medical Science, 2010)
This paper concerns orthodontic treatment of a 20 years old Bangladeshi female with bimaxillary proclination, localized spacing in the maxillary and mandibular arch and rotations in the central incisors of the mandibular arch. Orthodontic treatment carried out with preadjusted MBT type (018 slot) fixed brackets with alignment and retroclination of the maxillary and mandibular incisors to accomplish the treatment for esthetic improvement. The esthetics and occlusion were maintained after retention. Key words: Bimaxillary proclination; spacing; rotation; labial flaring. DOI: 10.3329/bjms.v8i4.4710 Bangladesh Journal of Medical Sciences Vol.8(4); October 2009 pp129-134